Allium brevipedicellatum (Amaryllidaceae), a new species from the Helan Mountains in China - Yang, Bo; Wang, Wenqiang; Dai, Rui; Xu, Hao; Alima,; Hao, Shuxiang; Fan, Yuke; Liang, Yongliang; Li, Xiaowei (Phytotaxa, 2025)
During a survey of plant diversity conducted in the Helan Mountains, an Allium species was discovered. The plant under consideration features narrowly linear, flat leaves measuring 1 mm in width, which are shorter than the scape; cylindrical, erect scape of 10–15 cm in height; hemispherical, compact umbels with 5–15 flowers; pedicels nearly equal in length, very short (1–2 mm long); and filaments shorter than the tepals. The plant was identified as Allium kansuense in the “Flora of Helan Mountains”. However, following a thorough review of the extant literature, it was determined that the original description of A. kansuense bears a strong resemblance to that of Allium sikkimense. Consequently, the amalgamation of A. kansuense into A. sikkimense is deemed substantiated. This newly defined species resembles A. bidentatum and A. tenuissimum morphologically but can be distinguished by the following diagnostic characteristics: it possesses a creeping rhizome with membranous, yellowish-brown outer bulb tunics; 2-angled scape; very short pedicels, only 1–2 mm long; and purplish-red perianth segments. The nomenclatural proposal is to designate this taxon as the new species Allium brevipedicellatum.